Leaf nitrogen is closely coupled to phenophases in a desert shrub ecosystem in China. (November 2015) - Chen, Zhi-Hao; Zha, Tianshan; Jia, Xin; Wu, Yajuan; Wu, Bin; Zhang, Yuqing; Guo, JianBin; Qin, ShuGao; Chen, Guopeng; Peltola, Heli
Abstract: The understanding of the seasonal dynamics of leaf nitrogen (N) relative to leaf traits for desert shrub species is limited. We investigated the seasonal changes in leaf N, soil N, specific leaf area (SLA) and photosynthetic capacity (Pmax ) in relation to the phenology of Artemisia ordosica in a desert shrubland area in northern China during the growing season of year 2012. We found that the amount of leaf N per unit dry mass varied in different phenological phases, having higher values during the early leaf expansion and leaf coloration and early defoliation periods and lower values during the expanded leaf and flowering periods. Pmax was positively related to leaf N from the late leaf expansion period to the flowering and bearing period. Photosynthetic nitrogen use efficiency (NUE) correlated with SLA during the growing period. However, similar relationships were not observed for the leaf expansion and defoliation periods. During the flowering and bearing period, leaf N content per unit dry mass remained relatively stable, although fluctuations occurred due to precipitation. Our findings could help with modelling the dynamics of plant-soil N coupling of desert shrub-land ecosystems under changing environment. Highlights: Leaf N per dry mass unit varied in different phenological phases. Leaf N content remained relatively stable in flowering and bearing phase. Photosynthetic capacity correlated leaf N in expanded leaf and flowering phase. Photosynthetic N use efficiency correlated SLA in expanded leaf & flowering phase.